Organizational Communication Model In Maintaining The Work Ethic Of Employees Of The Regional Revenue Agency Office Of Southeast Sulawesi Province - La Ode Mahbub; Jamallulail Jamallulail (Jurnal Ilmu Sosial Mamangan, 2024)
To maintain the Work Ethic of Employees, the communication model is one of the important things that need to be understood and applied appropriately to an organization or government agency. However, sometimes the communication model is not sufficiently understood and appropriate in its application so it has implications for mass communication in all members of the organization, both subordinates and superiors and so on. This research aims to analyze the application of the organizational communication model at the Regional Revenue Agency Office of Southeast Sulawesi Province and to analyze how to maintain employee work ethic related to the communication model. To analyze the communication model, Robbins (2013) uses the theory of the Chain Model, Wheel Model, Circle Model, Free Network Model (all channels), and the "Y" Letter Model. Meanwhile, to analyze the work ethic of employees, concepts from Siregar in Octarina (2013) are used, namely Awareness, Enthusiasm, Willpower, Commitment, Initiative, Productive, Improvement, and Insight. The results of the study showed that all of Robbins' theories were used at the Regional Revenue Agency Office in Southeast Sulawesi, but the more dominant one used was the Wheel Model (Well). Meanwhile, for work ethic, all of them are dominant and used well at the Southeast Sulawesi Regional Revenue Agency Office.